1998
DOI: 10.1046/j.1523-1747.1998.00360.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Antibodies Against Virus-Like Particles of Epidermodysplasia Verruciformis-Associated HPV8 in Patients at Risk of Skin Cancer

Abstract: There is increasing evidence for widespread occurrences of infection with Epidermodysplasia verruciformis-related human papillomaviruses, both in the general population and in immunosuppressed patients. In order to test for the prevalence of antibodies directed against the native L1 epitopes exposed on the surface of the virions, we have established an IgG-specific enzyme-linked immunosorbent assay with L1 virus-like particles of the Epidermodysplasia verruciformis-specific human papillomavirus 8 as antigen to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
50
2
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 32 publications
5
50
2
2
Order By: Relevance
“…In line with previous studies in Europe, the strongest associations were observed for HPV8 (20,29,30). Despite the small study population, statistical significance was reached for both the positive and the negative SCC association with HPV8 L1 and E6 seropositivity, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…In line with previous studies in Europe, the strongest associations were observed for HPV8 (20,29,30). Despite the small study population, statistical significance was reached for both the positive and the negative SCC association with HPV8 L1 and E6 seropositivity, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…85 (13) 134 (12) 56 (12) 59 (12) HPV49 170 (26) 269 (24) 130 (27) 138 (29) HPV75 113 (17) 174 (15) 79 (16) 84 (18) HPV76 103 (16) 149 (13) 75 (16) 72 (15) HPV80 110 (17) 208 (18) 74 (15) 89 (19) HPV92 84 (13) 142 (13) 60 (13) 66 (14) HPV93 21 (3) 29 (3) 15 (3) 12 ( (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Understanding the relationship between HPV and skin cancer is hampered by lack of knowledge about the appropriate measure of infection.…”
Section: Discussionmentioning
confidence: 99%
“…BetaPV L1 antibodies have been associated with both SCC and AK in casecontrol studies (6,(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), although the findings are somewhat inconsistent (reviewed in ref. 14).…”
Section: Introductionmentioning
confidence: 99%
“…Increased seroprevalences of HPV 8 have been reported among immunocompetent patients with SCC compared with patients with basaliomas or healthy controls (22)(23)(24). Antibodies to any of HPV 5,8,15,20,24, or 38 were more common among patients with a history of SCC (19.9%) than among controls (12.5%; P < 0.05; ref.…”
Section: Introductionmentioning
confidence: 97%